Catalysts and preparation methods for the ammoxidation of m-xylene to isophthalonitrile

By designing the synergistic effect of the active component V1.0CraXbYcZdOe and the modified silica support, the problems of insufficient activity and stability of existing catalysts were solved, and the efficient conversion of m-xylene to m-phthalonitrile was achieved, improving the selectivity and yield of the catalyst and meeting the requirements of industrial applications.

CN122252202APending Publication Date: 2026-06-23SULI (NINGXIA) NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610198563.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-11
Publication Date
2026-06-23

AI Technical Summary

Technical Problem

Existing catalysts for the ammoxidation of m-xylene to isophthalonitrile suffer from problems such as insufficient catalytic activity, poor adaptability, insufficient support strength, easy shedding of active components, and significant reactor scale-up effects, which affect the continuous and stable operation of industrial applications.

Method used

The active component with the general structural formula V1.0CraXbYcZdOe is adopted, where X is selected from B, P, As, and Se, Y is selected from Group VIII transition metals, and Z is selected from alkaline earth metals. Through electronic regulation and structural stability optimization, combined with modified silica support and zirconium oxide and potassium acetate modifiers, a synergistic catalytic effect is formed to improve the selectivity and yield of the catalyst.

Benefits of technology

It significantly improves the selectivity and yield of isophthalonitrile, the catalyst is environmentally friendly and non-toxic, the preparation process is simple, the wear index is low, and it meets the needs of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention relates to the field of catalyst technology, specifically to a catalyst for the ammoxidation of m-xylene to isophthalonitrile and its preparation method. It includes a support and an active ingredient, wherein the active ingredient has the general structural formula: V 1.0 Cr a X b Y c Z d O e Wherein: X is selected from at least one of B, P, As and Se; Y is selected from at least one of Group VIII transition metals; Z is selected from at least one alkaline earth metal. The catalyst prepared by the present invention is used for the ammoxidation of m-xylene to prepare isophthalonitrile, thereby improving the selectivity and yield of isophthalonitrile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, specifically to a catalyst for the ammoxidation of m-xylene to prepare isophthalonitrile and its preparation method. Background Technology

[0002] Isophthalonitrile (IPN) is an important raw material for fine organic chemicals with wide applications. Chlorination produces the highly efficient and low-toxicity fungicide chlorothalonil, while hydrogenation yields the high-performance epoxy resin curing agent m-phenylenediamine (MXDA). It can also be used to synthesize downstream products such as polyester resins, dyes, and pharmaceuticals, resulting in a large market demand and high application value. In the preparation process of IPN, the direct ammonia oxidation of m-xylene has become the mainstream technology due to its simple process and excellent economics. The core of this process lies in the development of high-performance ammonia oxidation catalysts. Vanadium-based catalysts are the most commonly used catalytic system in the m-xylene ammonia oxidation reaction, with V-Cr-based catalysts attracting widespread attention due to their simple preparation, good reproducibility, and high reactivity. Traditional V-Cr-based catalysts generally suffer from problems such as insufficient catalytic activity, poor adaptability, insufficient support strength, easy shedding of active components, and significant reactor scale-up effects, affecting continuous and stable operation in industrial applications. Therefore, developing an environmentally friendly, non-toxic, simple-to-prepare, highly selective, stable, and wear-resistant ammonia oxidation catalyst is of great significance for promoting the industrial upgrading of the m-xylene ammonia oxidation to isophthalonitrile process.

[0003] Chinese invention patent CN115041203B discloses a supported ammonia oxidation catalyst containing elements such as vanadium, chromium, thallium, and sulfur. It uses silicon carbide as a support, pre-treats the support through alkali and acid modification, and introduces elements such as thallium and sulfur to optimize the active components. This improves the catalyst's wear resistance and reaction stability to some extent and inhibits deep oxidation reactions. However, the active components of this patent include thallium, a highly toxic heavy metal. Thallium can easily cause environmental pollution and safety risks during catalyst preparation, use, and disposal, which is inconsistent with the development trend of green chemistry. Furthermore, the silicon carbide support used in this patent requires complex alkali-acid two-step modification treatment, which is cumbersome and increases preparation costs. The synergistic effect between the support and the active components still has room for optimization. Summary of the Invention

[0004] The first aspect of this invention provides a catalyst for the ammoxidation of m-xylene to prepare isophthalonitrile, comprising a support and an active component, wherein the active component has the general structural formula: V 1.0 Cr a X b Y c Z d O eWherein: X is selected from at least one of B, P, As and Se; Y is selected from at least one of Group VIII transition metals; Z is selected from at least one of alkaline earth metals; a, b, c, d and e represent the atomic ratios of the corresponding elements; the value of a ranges from 2.0 to 4.0, the value of b ranges from 0.02 to 0.10, the value of c ranges from 0.2 to 0.8, and the value of d ranges from 0.3 to 0.6; e is the number of oxygen atoms required to satisfy the oxidation states of each element in the active ingredient.

[0005] Existing catalysts for the ammoxidation of m-xylene to prepare isophthalonitrile suffer from problems such as unreasonable active component combinations and weak inter-element synergistic effects, making it difficult to balance selectivity and yield of isophthalonitrile. This invention addresses the reaction characteristics of the ammoxidation of m-xylene to prepare isophthalonitrile by designing a catalyst with the general structural formula V... 1.0 Cr a X b Y c Z d O e The active component, with vanadium as its core active center, provides a key reaction site for the ammonia oxidation reaction. Chromium, by forming a stable multi-component oxide structure with vanadium, regulates the electron distribution and dispersion state of the active center, preventing vanadium species aggregation and deactivation, while simultaneously enhancing the redox cycle efficiency of vanadium. Element X not only optimizes the strength and distribution of acidic sites in the catalyst but also synergistically enhances the structural stability of the active center with chromium, promoting the adsorption and activation of m-xylene molecules at the active site. Group VIII transition metal Y forms a synergistic catalytic site with vanadium, strengthening the CH bond breaking and ammonia activation process, guiding the reaction to the directional formation of isophthalonitrile, and reducing side reactions. Chromium's regulation of the electronic state further enhances the electron transfer efficiency between Y and vanadium. Alkaline earth metal Z, on the one hand, enhances the catalyst's resistance to carbon deposition and mechanical strength by forming a stable lattice structure with X and chromium, preventing active sites from being covered by carbon deposits. On the other hand, it can regulate the electronic environment on the catalyst surface, synergistically optimizing the product desorption rate with vanadium and Y, preventing deep oxidation of the target product. Through multi-dimensional synergistic effects such as electronic regulation, structural stabilization, and directional reaction guidance, the elements comprehensively improve the reaction kinetics, promote the efficient conversion of m-xylene to m-phthalonitrile, and thus significantly improve the selectivity and yield of the target product.

[0006] Optionally, the value of a ranges from 3.0 to 4.0, the value of b ranges from 0.02 to 0.08, the value of c ranges from 0.2 to 0.5, the value of d ranges from 0.3 to 0.4, and e is the number of oxygen atoms required to satisfy the oxidation states of each element in the active ingredient.

[0007] Optionally, the Group VIII transition metal includes at least one of Fe, Co, Ni, and Rh.

[0008] Optionally, the alkaline earth metal includes at least one of Be, Mg, Ca, Sr and Ba.

[0009] The raw materials for preparing the active ingredient include: V2O5, CrO3, the inorganic acid corresponding to X, the oxide corresponding to Y, the oxide corresponding to Z, and complexed organic acids.

[0010] Optionally, the structural formula of the active ingredient is: V 1.0 Cr 3.0-4.0 B 0.02-0.08 Co 0.2-0.5 Be 0.3-0.4 O e ; where e is the number of oxygen atoms required to satisfy the oxidation states of each element in the active ingredient.

[0011] Optionally, the complexed organic acid includes at least one of oxalic acid, citric acid, tartaric acid, maleic acid, malic acid, succinic acid, and gluconic acid.

[0012] The carrier comprises modified silica.

[0013] The modified silica component includes silica and a modifier.

[0014] Optionally, the precursor of the silica is selected from silica sol.

[0015] The modifier includes metal oxides and organometallic acid salts, wherein the content of metal oxides in the carrier is 0.3-3 wt%.

[0016] The metal oxide includes at least one of rare earth metal oxides and transition metal oxides.

[0017] The organometallic acid salts include at least one of alkaline earth organometallic acid salts and alkali metal organometallic acid salts.

[0018] Optionally, the rare earth metal oxide includes at least one of lanthanum oxide, cerium oxide, yttrium oxide, neodymium oxide, praseodymium oxide, and terbium oxide.

[0019] Optionally, the transition metal oxide includes at least one of zirconium oxide, titanium oxide, niobium oxide, molybdenum oxide, tungsten oxide, and tantalum oxide.

[0020] Optionally, the alkaline earth metal organoacid salt includes at least one of magnesium acetate, calcium acetate, strontium acetate, barium acetate, magnesium malonate, and calcium succinate.

[0021] Optionally, the alkali metal organophosphate includes at least one of potassium acetate, lithium acetate, sodium acetate, potassium propionate, sodium butyrate, and potassium isobutyrate.

[0022] Optionally, the modifier includes zirconium oxide and potassium acetate.

[0023] Optionally, the average particle size of the zirconium oxide is 5-80 nm.

[0024] Optionally, the average particle size of the zirconium oxide is 5-40 nm.

[0025] Optionally, the average particle size of the zirconium oxide is 20-40 nm.

[0026] The weight ratio of zirconium oxide to potassium acetate is 1:(1-8).

[0027] This invention achieves synergistic optimization of catalytic efficiency and mechanical properties by limiting the modifier to zirconium oxide and potassium acetate, with their weight ratio controlled at 1:(1-8). Zirconia itself possesses high hardness and high structural stability, and as a modifier, it can directly fill the pore structure of the catalyst matrix, forming a rigid support framework and enhancing the overall structural strength of the catalyst particles, laying the foundation for improved mechanical properties. The potassium ions in potassium acetate can act as an interface regulator, improving the compatibility between zirconium oxide and the catalyst matrix, promoting uniform dispersion of zirconium oxide in the matrix, and avoiding stress concentration caused by local agglomeration. Furthermore, by adjusting the electronic environment and interfacial binding energy on the catalyst surface, it strengthens the bonding between particles, reducing particle shedding and wear during catalysis. Within a specific weight ratio range, the two form a highly efficient synergistic effect, fully utilizing their dispersion and bonding effects to ensure uniform distribution of zirconium oxide to maximize rigid support, while avoiding excessive coverage of the catalyst's active sites by potassium acetate. Thus, while maintaining catalytic efficiency, it significantly improves the catalyst's wear resistance; according to ASTM D-5757 standard testing, its wear index can be controlled to ≤0.5%.

[0028] Optionally, the weight ratio of zirconium oxide to potassium acetate is 1:(1-4).

[0029] The support is 60-90 wt% of the catalyst weight.

[0030] Optionally, the support is 70-80 wt% of the catalyst weight.

[0031] The modifier content in the carrier accounts for 0.2-8 wt% of the carrier weight. Optionally, the modifier content in the carrier accounts for 0.5-4 wt% of the carrier weight.

[0032] The second aspect of this invention provides a method for preparing a catalyst, comprising the following steps: adding V2O5 and CrO3, the oxide corresponding to Y, and the oxide corresponding to Z to water, stirring evenly and heating, adding a complexed organic acid to form a colloid; adding the inorganic acid corresponding to X to water, stirring to dissolve, and then adding it to the colloid to obtain a mixed colloid containing active ingredients; adding a metal oxide to a dispersant to form a sol, adding the sol to a silica sol, dissolving an organometallic acid salt in water and adding it to the silica sol to prepare a support; adding the support to the mixed colloid containing active ingredients, dispersing evenly, adjusting the solid content to obtain a catalyst slurry; and sequentially drying and calcining the catalyst slurry to obtain the catalyst.

[0033] The dispersant includes a weakly basic amine dispersant.

[0034] Optionally, the weakly basic amine dispersant includes at least one of ethanolamine, ethylenediamine, and propylamine.

[0035] The catalyst has a particle size of 30-100 μm.

[0036] Optionally, the particle size of the catalyst is 50-80 μm.

[0037] The adjustment of solid content is achieved using an evaporation and concentration process.

[0038] Optionally, the evaporation and concentration temperature is 90-110°C.

[0039] The catalyst slurry has a solid content of 30-50 wt%.

[0040] Optionally, the catalyst slurry has a solids content of 35-45 wt%.

[0041] The drying includes spray drying.

[0042] The parameters for spray drying include: an inlet temperature of 280-300℃ and an outlet temperature of 140-170℃.

[0043] Optionally, the parameters of the spray drying include: the spray drying inlet temperature is 290-300℃ and the outlet temperature is 150-170℃.

[0044] The roasting process employs a segmented roasting technique.

[0045] The roasting process employs a 3-6 stage roasting process.

[0046] The roasting process employs a four-stage roasting process, with specific process parameters including: Stage I roasting temperature of 200-250℃ and roasting time of 5-10h; Stage II roasting temperature of 340-380℃ and roasting time of 10-15h; Stage III roasting temperature of 400-450℃ and roasting time of 4-8h; and Stage IV roasting temperature of 500-580℃ and roasting time of 10-15h.

[0047] Optionally, the roasting process adopts a four-stage roasting process, with specific process parameters including: Stage I roasting temperature of 200-230℃ and roasting time of 5-8h; Stage II roasting temperature of 340-360℃ and roasting time of 12-15h; Stage III roasting temperature of 400-430℃ and roasting time of 4-6h; and Stage IV roasting temperature of 520-580℃ and roasting time of 10-12h.

[0048] Beneficial effects 1. This invention defines the structural formula of the active ingredient as: V 1.0 Cr a X b Y c Z d O e Wherein: X is selected from at least one of B, P, As and Se, Y is selected from at least one of Group VIII transition metals, and Z is selected from at least one of alkaline earth metals. It can be used to prepare isophthalonitrile by ammoxidation of m-xylene, thereby improving the selectivity and yield of isophthalonitrile.

[0049] 2. This invention defines the structural formula of the active ingredient as: V 1.0 Cr 3.0-4.0 B 0.02-0.08 Co 0.2-0.5 Be 0.3- 0.4 O e It is used for the ammoxidation of m-xylene to prepare isophthalonitrile, and the selectivity and yield of isophthalonitrile can reach over 90%.

[0050] 3. The present invention defines the carrier as modified silica, the modified silica as comprising silica and a modifier, wherein the precursor of silica is selected from silica sol, and the modifier comprises metal oxides and organometallic acid salts, wherein the content of metal oxides in the carrier is 0.3-3 wt%, which can improve the strength of the catalyst.

[0051] 4. By limiting the modifiers to include zirconium oxide and potassium acetate, and the weight ratio of zirconium oxide to potassium acetate is 1:(1-8), the mechanical properties of the catalyst can be further improved while maintaining the catalytic efficiency. The wear index is ≤0.5% when tested according to ASTM D-5757 standard.

[0052] 5. The catalyst of this invention is environmentally friendly, non-toxic, and has a simple preparation process. Detailed Implementation

[0053] Example 1 A catalyst for the ammoxidation of m-xylene to isophthalonitrile comprises 70 wt% support and 30 wt% active ingredient, wherein the active ingredient has the general structural formula: V 1.0 Cr 3.0 B 0.05 Co 0.4 Be 0.3 O 12.28 .

[0054] The raw materials for preparing the active ingredient include: V2O5, CrO3, CoO, BeO, boric acid, complexed organic acid (oxalic acid), and water; the carrier is modified silica, which consists of silica and a modifier; the precursor of the silica is selected from 40wt% silica sol (solute is silica, solvent is water); the modifier is zirconium oxide (average particle size 30nm) and potassium acetate, with a weight ratio of zirconium oxide to potassium acetate of 1:1, wherein the zirconium oxide content in the carrier is 0.5wt%.

[0055] A method for preparing a catalyst includes the following steps: 100.0g of V2O5, 329.7g of CrO3, 33.0g of CoO, and 8.2g of BeO were added to 2000g of water, stirred until homogeneous, and heated to 75℃. 910.0g of oxalic acid was then added to form a colloid. 3.41g of boric acid was added to 100g of water, stirred until dissolved, and then added to the colloid to obtain a colloid mixture containing active ingredients. 5.5g of zirconium oxide was added to 200.0g of dispersant (25wt% aqueous ethanolamine solution) and dispersed evenly to form a sol. The resulting sol was added dropwise to 2739g of silica sol while stirring. 5.5g of potassium acetate was dissolved in 200g of water and added to the silica sol in the same way to prepare the carrier (the silica sol temperature was heated and maintained at 50-60℃ throughout the process). The carrier was added to a colloid mixture containing active ingredients, and the temperature was maintained at 70-80℃. The mixture was stirred and kept at this temperature for 1 hour, then heated to 100℃ and evaporated and concentrated to obtain a catalyst slurry with a solid content of 40wt%. The catalyst slurry was then subjected to spray drying (inlet temperature 300℃, outlet temperature 160℃, particle size controlled at 50-80 micrometers) and calcination (stages I-IV calcination process: stage I calcination temperature 200℃, calcination time 6 hours; stage II calcination temperature 350℃, calcination time 12 hours; stage III calcination temperature 400℃, calcination time 5 hours; stage IV calcination temperature 550℃, calcination time 12 hours) to obtain the catalyst.

[0056] Example 2 The specific implementation method is the same as in Example 1; the difference is that the zirconium oxide content in the carrier is 1 wt%.

[0057] Example 3 The specific implementation method is the same as in Example 1; the difference is that the zirconium oxide content in the carrier is 1.5 wt%.

[0058] Example 4 The specific implementation method is the same as in Example 1; the difference is that the zirconium oxide content in the carrier is 2wt%.

[0059] Example 5 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of zirconium oxide and potassium acetate is 1:2, and the zirconium oxide content in the carrier is 1 wt%.

[0060] Example 6 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of zirconium oxide to potassium acetate is 1:3, and the zirconium oxide content in the carrier is 0.75wt%.

[0061] Example 7 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of zirconium oxide to potassium acetate is 1:4, and the zirconium oxide content in the carrier is 0.6wt%.

[0062] Example 8 The specific implementation method is the same as in Example 1; the difference is that the proportions of Cr, B, Co, and Be in the active ingredient are adjusted, and the general structural formula of the active ingredient is: V 1.0 Cr 3.5 B 0.08 Co 0.3 Be 0.3 O 13.72 .

[0063] Example 9 The specific implementation method is the same as in Example 1; the difference is that the proportions of Cr, B, Co, and Be in the active ingredient are adjusted, and the general structural formula of the active ingredient is: V 1.0 Cr 3.2 B 0.04 Co 0.5 Be 0.4 O 13.06 .

[0064] Example 10 The specific implementation method is the same as in Example 1; the difference is that the types of elements X, Y, and Z in the active ingredient are adjusted, boric acid is replaced with phosphoric acid, CoO is replaced with NiO, and BeO is replaced with MgO; the general structural formula of the active ingredient is: V 1.0 Cr 3.0 P 0.04 Ni0.5 Mg 0.4 O 12.5 .

[0065] Example 11 The specific implementation method is the same as in Example 1; the difference is that the types of elements X and Z in the active ingredient are adjusted, boric acid is replaced with phosphoric acid, and BeO is replaced with CaO; the general structural formula of the active ingredient is: V 1.0 Cr 3.0 P 0.04 Co 0.5 Ca 0.4 O 12.5 .

[0066] Example 12 The specific implementation method is the same as in Example 1; the difference is that the types of Y and Z elements in the active ingredient are adjusted, CoO is replaced with NiO, and BeO is replaced with MgO; the general structural formula of the active ingredient is: V 1.0 Cr 3.0 B 0.04 Ni 0.5 Mg 0.4 O 12.46 .

[0067] Comparative Example 1 The specific implementation method is the same as in Example 1; the difference is that no modifier is used.

[0068] Comparative Example 2 The specific implementation method is the same as in Example 1; the difference is that the modifier is only zirconium oxide, and the zirconium oxide content in the carrier is 0.5 wt%.

[0069] Comparative Example 3 The specific implementation method is the same as in Example 1; the difference is that the modifier is only zirconium oxide, and the zirconium oxide content in the carrier is 1 wt%.

[0070] Comparative Example 4 The specific implementation method is the same as in Example 1; the difference is that the modifier is only zirconium oxide, and the zirconium oxide content in the carrier is 2wt%.

[0071] Comparative Example 5 The specific implementation method is the same as in Example 1; the difference is that the modifier is only potassium acetate, and the potassium acetate content in the carrier is 1 wt%.

[0072] Comparative Example 6 The specific implementation method is the same as in Example 1; the difference is that the modifier is only potassium acetate, and the potassium acetate content in the carrier is 1.5 wt%.

[0073] Comparative Example 7 The specific implementation method is the same as in Example 1; the difference is that the modifier is only potassium acetate, and the potassium acetate content in the carrier is 2wt%.

[0074] Comparative Example 8 A catalyst comprising 70 wt% support and 30 wt% active ingredient, wherein the active ingredient has the general structural formula: V 1.0 Cr 3.0 B 0.05 Co 0.4 O 11.98 .

[0075] The raw materials for preparing the active ingredient include: V2O5, CrO3, CoO, boric acid, complexed organic acid (oxalic acid), and water; the carrier is modified silica, and the modified silica consists of silica and a modifier; the precursor of the silica is selected from 40wt% silica sol (solute is silica, solvent is water); the modifier is zirconium oxide (average particle size 30nm) and potassium acetate, and the weight ratio of zirconium oxide to potassium acetate is 1:1, wherein the zirconium oxide content in the carrier is 0.5wt%.

[0076] A method for preparing a catalyst includes the following steps: 100.0g of V2O5, 329.7g of CrO3, and 33.0g of CoO were added to 2000g of water, stirred until homogeneous, and heated to 75℃. 910.0g of oxalic acid was then added to form a colloid. 3.41g of boric acid was added to 100g of water, stirred until dissolved, and then added to the colloid to obtain a colloid mixture containing active ingredients. 5.5g of zirconium oxide was added to 200.0g of dispersant (25wt% aqueous ethanolamine solution) and dispersed evenly to form a sol. The resulting sol was added dropwise to 2739g of silica sol while stirring. 5.5g of potassium acetate was dissolved in 200g of water and added to the silica sol in the same way to prepare the carrier (the silica sol temperature was heated and maintained at 50-60℃ throughout the process). The carrier was added to a colloid mixture containing active ingredients, and the temperature was maintained at 70-80℃. The mixture was stirred and kept at this temperature for 1 hour, then heated to 100℃ and evaporated and concentrated to obtain a catalyst slurry with a solid content of 40wt%. The catalyst slurry was then subjected to spray drying (inlet temperature 300℃, outlet temperature 160℃, particle size controlled at 50-80 micrometers) and calcination (stages I-IV calcination process: stage I calcination temperature 200℃, calcination time 6 hours; stage II calcination temperature 350℃, calcination time 12 hours; stage III calcination temperature 400℃, calcination time 5 hours; stage IV calcination temperature 550℃, calcination time 12 hours) to obtain the catalyst.

[0077] Comparative Example 9 A catalyst comprising 70 wt% support and 30 wt% active ingredient, wherein the active ingredient has the general structural formula: V 1.0 Cr 3.0 B 0.05 Be 0.3 O 12.28 .

[0078] The raw materials for preparing the active ingredient include: V2O5, CrO3, BeO, boric acid, complexed organic acid (oxalic acid), and water; the carrier is modified silica, which consists of silica and a modifier; the precursor of the silica is selected from 40wt% silica sol (solute is silica, solvent is water); the modifier is zirconium oxide (average particle size 30nm) and potassium acetate, with a weight ratio of zirconium oxide to potassium acetate of 1:1, wherein the zirconium oxide content in the carrier is 0.5wt%.

[0079] A method for preparing a catalyst includes the following steps: 100.0g of V2O5, 329.7g of CrO3, and 8.2g of BeO were added to 2000g of water, stirred until homogeneous, and heated to 75℃. 910.0g of oxalic acid was then added to form a colloid. 3.41g of boric acid was added to 100g of water, stirred until dissolved, and then added to the colloid to obtain a colloid mixture containing active ingredients. 5.5g of zirconium oxide was added to 200.0g of dispersant (25wt% aqueous ethanolamine solution) and dispersed evenly to form a sol. The resulting sol was added dropwise to 2739g of silica sol while stirring. 5.5g of potassium acetate was dissolved in 200g of water and added to the silica sol in the same way to prepare the carrier (the silica sol temperature was heated and maintained at 50-60℃ throughout the process). The carrier was added to a colloid mixture containing active ingredients, and the temperature was maintained at 70-80℃. The mixture was stirred and kept at this temperature for 1 hour, then heated to 100℃ and evaporated and concentrated to obtain a catalyst slurry with a solid content of 40wt%. The catalyst slurry was then subjected to spray drying (inlet temperature 300℃, outlet temperature 160℃, particle size controlled at 50-80 micrometers) and calcination (stages I-IV calcination process: stage I calcination temperature 200℃, calcination time 6 hours; stage II calcination temperature 350℃, calcination time 12 hours; stage III calcination temperature 400℃, calcination time 5 hours; stage IV calcination temperature 550℃, calcination time 12 hours) to obtain the catalyst.

[0080] Comparative Example 10 A catalyst comprising 70 wt% support and 30 wt% active ingredient, wherein the active ingredient has the general structural formula: V 1.0 Cr 3.0 Co 0.4 Be 0.3 O12.20 .

[0081] The raw materials for preparing the active ingredient include: V2O5, CrO3, CoO, BeO, complexed organic acid (oxalic acid), and water; the carrier is modified silica, which consists of silica and a modifier; the precursor of the silica is selected from 40wt% silica sol (solute is silica, solvent is water); the modifier is zirconium oxide (average particle size 30nm) and potassium acetate, with a weight ratio of zirconium oxide to potassium acetate of 1:1, wherein the zirconium oxide content in the carrier is 0.5wt%.

[0082] A method for preparing a catalyst includes the following steps: Add 100.0g of V2O5, 329.7g of CrO3, 33.0g of CoO and 8.2g of BeO to 2000g of water, stir evenly, heat to 75℃, add 910.0g of oxalic acid, and disperse evenly to obtain a colloid containing active ingredients. 5.5g of zirconium oxide was added to 200.0g of dispersant (25wt% aqueous ethanolamine solution) and dispersed evenly to form a sol. The resulting sol was added dropwise to 2739g of silica sol while stirring. 5.5g of potassium acetate was dissolved in 200g of water and added to the silica sol in the same way to prepare the carrier (the silica sol temperature was heated and maintained at 50-60℃ throughout the process). The carrier was added to a colloid mixture containing active ingredients, and the temperature was maintained at 70-80℃. The mixture was stirred and kept at this temperature for 1 hour, then heated to 100℃ and evaporated and concentrated to obtain a catalyst slurry with a solid content of 40wt%. The catalyst slurry was then subjected to spray drying (inlet temperature 300℃, outlet temperature 160℃, particle size controlled at 50-80 micrometers) and calcination (stages I-IV calcination process: stage I calcination temperature 200℃, calcination time 6 hours; stage II calcination temperature 350℃, calcination time 12 hours; stage III calcination temperature 400℃, calcination time 5 hours; stage IV calcination temperature 550℃, calcination time 12 hours) to obtain the catalyst.

[0083] Comparative Example 11 The specific implementation method is the same as in Example 1; the difference is that the zirconium oxide content in the carrier is 5wt% and the potassium acetate content is 5wt%.

[0084] Comparative Example 12 The specific implementation method is the same as in Example 1; the difference is that the zirconium oxide content in the carrier is 0.2wt% and the potassium acetate content is 0.2wt%.

[0085] Comparative Example 13 The specific implementation method is the same as in Example 1; the difference is that the proportions of Cr, B, Co, and Be in the active ingredient are adjusted, and the general structural formula of the active ingredient is: V1.0 Cr 1.8 B 0.15 Co 0.1 Be 0.2 O 8.43 .

[0086] Comparative Example 14 The specific implementation method is the same as in Example 1; the difference is that the proportions of Cr, B, Co, and Be in the active ingredient are adjusted, and the general structural formula of the active ingredient is: V 1.0 Cr 5.0 B 0.20 Co 0.1 Be 0.1 O 18 .

[0087] Comparative Example 15 The specific implementation method is the same as in Example 1; the difference is that the spray drying inlet temperature is adjusted to 230°C and the outlet temperature to 120°C.

[0088] Comparative Example 16 The specific implementation method is the same as in Example 1; the difference is that the roasting process temperature is adjusted (roasting process of stages I-IV: stage I roasting temperature is 200℃, roasting time is 6h; stage II roasting temperature is 300℃, roasting time is 12h; stage III roasting temperature is 380℃, roasting time is 5h; stage IV roasting temperature is 460℃, roasting time is 12h). Performance testing methods The catalysts prepared in the examples and comparative examples were subjected to activity evaluation and wear index testing, and the test data are listed in Table 1.

[0089] 1. The catalyst activity evaluation was conducted in a fluidized bed reactor with an inner diameter of 28 mm. 150 g of catalyst was loaded into the fluidized bed reactor, and a feed gas mixture with a molar ratio of m-xylene:ammonia:air = 1:6.5:32 was introduced for the reaction. The reaction temperature was 410℃, the reaction pressure was 5 kPaG, and the m-xylene loading of the catalyst was WWH = 0.05 h⁻¹. -1 After the reaction proceeded for 200 hours, the gas exiting the reaction was effectively captured, and the products were analyzed by gas chromatography. The selectivity and yield of isophthalonitrile were calculated. The selectivity of isophthalonitrile (%) = (moles of isophthalonitrile produced / moles of m-xylene reacted) × 100%; the yield of isophthalonitrile (%) = (moles of isophthalonitrile produced / moles of m-xylene fed) × 100%.

[0090] 2. The abrasion index of the catalyst was tested and calculated using the ASTM D5757 standard.

[0091] Performance test data Table 1

[0092] The data from Example 2 and Comparative Examples 8-10 show that the combination of B, Co, and Be elements has a synergistic effect on improving the selectivity and yield of isophthalonitrile in the catalyst with V and Cr as the main components, and can play a role in co-catalysis. A comparison of the data from Examples 1-7 and Comparative Example 1 shows that the catalyst prepared from silica sol after in-situ modification with zirconium oxide and potassium acetate can significantly improve the selectivity and yield of isophthalonitrile and reduce the wear index. A comparison of the data from Example 1 and Comparative Examples 11-14 shows that the catalyst prepared can only achieve good performance when the ratio of the carrier modifier zirconium oxide and potassium acetate and the contents of the three elements X, Y, and Z are within the requirements of the claims. A comparison of the data from Example 1 and Comparative Examples 15-16 shows that the catalyst prepared can only achieve good performance when the spray drying and calcination temperatures are within the range required by the claims. A comparison of the data from Examples 1, 2, 4 and Comparative Examples 1-7 shows that the catalyst prepared by in-situ modification of silica sol with zirconium oxide alone can reduce the wear index, but cannot improve the selectivity and yield of isophthalonitrile; the catalyst prepared by in-situ modification of silica sol with potassium acetate alone has no significant effect on reducing the wear index and improving the selectivity and yield of isophthalonitrile; it is evident that nano-sized zirconium oxide and potassium acetate have a synergistic effect in improving the selectivity and stability of the catalyst.

Claims

1. A catalyst for the ammoxidation of m-xylene to prepare isophthalonitrile, characterized in that, It includes a carrier and an active ingredient, wherein the general structural formula of the active ingredient is: V 1.0 Cr a X b Y c Z d O e Wherein: X is selected from at least one of B, P, As and Se; Y is selected from at least one of Group VIII transition metals; Z is selected from at least one of alkaline earth metals; a, b, c, d and e represent the atomic ratios of the corresponding elements; the value of a ranges from 2.0 to 4.0, the value of b ranges from 0.02 to 0.10, the value of c ranges from 0.2 to 0.8, and the value of d ranges from 0.3 to 0.6; e is the number of oxygen atoms required to satisfy the oxidation states of each element in the active ingredient.

2. The catalyst according to claim 1, characterized in that, The raw materials for preparing the active ingredient include: V2O5, CrO3, the inorganic acid corresponding to X, the oxide corresponding to Y, the oxide corresponding to Z, the complexed organic acid, and water.

3. The catalyst according to claim 2, characterized in that, The general structural formula of the active ingredient is: V 1.0 Cr 3.0- 4.0 B 0.02-0.08 Co 0.2-0.5 Be 0.3-0.4 O e ; where e is the number of oxygen atoms required to satisfy the oxidation states of each element in the active ingredient.

4. The catalyst according to claim 3, characterized in that, The carrier includes modified silica, and the modified silica comprises silica and a modifier.

5. The catalyst according to claim 4, characterized in that, The precursor of the silica is selected from silica sol.

6. The catalyst according to claim 4, characterized in that, The modifier includes metal oxides and organometallic acid salts, wherein the content of metal oxides in the carrier is 0.3-3 wt%.

7. The catalyst according to claim 6, characterized in that, The modifier comprises zirconium oxide and potassium acetate, wherein the weight ratio of zirconium oxide to potassium acetate is 1:(1-8), and the average particle size of the zirconium oxide is 5-80 nm.

8. A method for preparing the catalyst according to any one of claims 2-7, characterized in that, Includes the following steps: The oxides of V₂O₅, CrO₃, Y, and Z were added to water, stirred until homogeneous, and heated. A complexed organic acid was then added to form a colloid. The inorganic acid corresponding to X was added to water, stirred until dissolved, and then added to the colloid to obtain a mixed colloid containing active ingredients. The metal oxide was added to a dispersant to form a sol, which was then added to a silica sol. The organometallic acid salt was dissolved in water and added to the silica sol to prepare a support. The support was added to the mixed colloid containing active ingredients, dispersed evenly, and the solid content was adjusted to obtain a catalyst slurry. The catalyst slurry was then dried and calcined to obtain the catalyst.

9. The method for preparing the catalyst according to claim 8, characterized in that, The drying includes spray drying.

10. The method for preparing the catalyst according to claim 8, characterized in that, The roasting process employs a segmented roasting technique.

Citation Information

Patent Citations

  • Ammonia oxidation catalyst, preparation method and application thereof

    CN115041203B